Analysis of Students’ Reading Comprehension of Descriptive Text at SMK Negeri 2 Pematangsiantar - Sinaga, Astrid Sri Rasta (Lembaga Riset Mutiara Akbar, 2022)
This research aims to find out how is the students’ Reading Comprehension of Descriptive Text. And what are their difficulties in Reading Comprehension.The method used in this research is a qualitative method, the research was conducted at SMK N2 PEMATANGSIANTAR with the samples were 35 students The researcher used five stories of descriptive text and fifty questions about the text,and there searcher used interview test too. The data collection was taken from the sudents’ score. The result of the research showed that there is 0 studentor 0% who was categorized exellent,there were 2 students or 5,7%who were categorized as very good,there were 7 studentsor 20% who were categorized as good, there were 14 students or 40 % who were categorized as fair, there were 8 students or 22,8 % who were categorized as poor, there were 4 students or 11,4 % who were categorized as very poor. And the researcher found the average by the score was 61,8 % . So, fromthe result the researcher can conclude that the students were still in the fair category